Javanese-Pragmatic Transfer in the English Exclamations by Jang Hansol - Siagian, Sinta Uli (English Literature Study Program, 2024)
Someone who can speak a foreign language is likely to do pragmatic transfer. The pragmatic transfer is when a speaker applies the social and cultural norms of his first language when using a second language (Sofwan, 2014; Saleem et al., 2020; Bu, 2022). This research analyzes the phenomenon of Javanese pragmatic transfer in the English exclamation of a YouTuber named Jang Hansol on his channel